InChI: a user’s perspective - Bachrach Steven M (Journal of Cheminformatics, 2012)
Abstract Exchange of chemical structures between practicing chemists is essential to chemical communication. The International Chemical Identifier (InChI) provides a means for lossless communication of structures without resort to any proprietary software or databases nor does it require any payment or royalty fees. This perspective describes why the InChI is valuable to all chemists and how it will be an essential component of creating the chemical web.